Urban Archaeology at a Crossroads - Jeroen Bouwmeester (Internet Archaeology)
Since the Second World War, archaeological remains in towns have come under increasing pressure: major construction works have led to considerable degradation of the archaeological record. From the 1970s onwards, there has been growing awareness of the vulnerability of archaeology in old towns, yet it was not until the introduction of the Malta legislation in 1992 that archaeological research in towns really took off. In the Netherlands, however, application of the legislation also has an obvious downside. With research being mainly documentary in character, synthesising research is lagging behind. In addition, it is not always clear where within the 19th- and 20th-century urban expansion archaeology can be expected, and what type of remains there will be. The effect of construction on the remains has also remained unclear for a long period of time. Research by the Cultural Heritage Agency of the Netherlands has provided important insight into this. As a result, this article provides an agenda to address some of the key challenges faced by the field of urban archaeology.